Studi Eksploratif Smart Learning Environment dan Implikasinya terhadap Pengelolaan Pembelajaran Digital di STKIP YPUP - Sangkala Sirate, Sitti Fatimah; Mulyati; Muhammad Yaumi (Jurnal Diskursus Islam, 2025)
This study aims to explore the concept of Smart Learning Environment (SLE) and analyze its implications for digital learning management at STKIP YPUP. The study employed a qualitative approach using an exploratory library research design. Data were collected from various academic sources, including books, journal articles, digital repositories, and academic search engines related to smart learning, smart education, smart pedagogy, smart technology, and smart classroom. Data analysis was conducted using the Miles, Huberman, and Saldana model through the stages of data condensation, data display, verification, and conclusion drawing. The findings indicate that Smart Learning Environment is a technology-based learning environment characterized by self-directed, motivated, adaptive, resource-enriched, and technology-embedded learning. Furthermore, SLE has implications for digital learning management through enhancing learning flexibility, integrating smart technologies, strengthening interactivity, and developing the roles of lecturers and students within digital learning environments in higher education.